Characteristics of the Artistic Construction of Light and Color Focus in the Theater Performance: محمد عزيز حسن (Al-Academy, 2019)
The theater has a living environment that resembles or realistically simulates the real life environment on the stage where we see the place, light and living being as elements representing a picture of the life scene and for a period of time the theater merely conveyed that image, but with the development of the world industrially and technologically, the perception of this picture has evolved with the emergence of intellectual progress where each part has advantages and Philosophical goals that are consistent with the evolution of form. The theatrical lighting, colors and landscapes have become parts in the composition of a new life component in form and content and based on the above this research is titled (the characteristics of the artistic construction of light and color focus in the theater performance). The problem of the research is focusing on the subject of treatments in the field of color and light within the theatrical performance, which needs a lot of study and research for the purpose of establishing the foundations and criteria for it, especially as it is a modern subject that needs extensive studies. The research was based on the following question: (What are the characteristics of the artistic construction of light and color focus in the theatrical performance?) The aim of the research is to identify those characteristics that focused on making these two elements a goal in the process of focus, whether on the actor or theatrical scene, through the successful experience in the field of this type of theater, whether in Iraq or elsewhere. Given the importance of focusing on the aesthetics of the acting performance and theater scene by light and color and even the lines of the design of the theater scene, the importance of research lies in how to use this process and identify the treatments and problems within this topic and to reach the optimal uses of the focus process. The objective limits of the research are the characteristics of the intellectual and aesthetic dimensions of the focus of light and color in the theatrical performance, while the spatial limit is the theater of the Division of Art and Cultural Activities in the presidency of the University of Baghdad, while the temporal limit is the year 2015. The importance and limits of the research as well as the definition of terms have been included.The theoretical framework consists of three sections, the first is (intensity and abundance of light as a photo concentration element) and the second section (characteristics of light exposure and its impact on the scene), while the third section includes the topic (aesthetics of color concentration in theatrical lighting). The researcher followed the descriptive approach and the method of content analysis. For the purpose of analyzing the sample, the theoretical framework, which tackles the literature related to the subject of the research, was utilized to contribute to the achievement of the research objective. The research used samples such as (the play of the birds' owner in wasted time) and (the play of shelters). The analysis was based on them. The researcher presented the most important findings and conclusions reached at , and one of the results obtained by the researcher was that in the case of the presence of many symbols and connotations within the presentation this requires the use of light and color focus in order to give the group of symbols or each individual symbol its symbolic and semantic value in a manner that fits its philosophical strength to enhance its presence as a point of attract to the recipient during the theater performance.